Securing Cloud Services: A pragmatic approach to security architecture in the Cloud - Newcombe, Lee (IT Governance Publishing, 2012)
This book provides an overview of security architecture processes and explains how they may be used to derive an appropriate set of security controls to manage the risks associated with working in the Cloud. Part 1 introduces Cloud Computing and describes the main service models (IaaS, PaaS and SaaS) and deployment models (public, private, community and hybrid) as defined by NIST. It outlines the common benefits, and describes some of the potential pitfalls of, and threats associated with, Cloud Computing. Part 2 outlines security architecture concepts and describes how they relate to Cloud Computing. It uses a conceptual security reference model (SRM) to define a set of common security services and explains how they can be delivered across the various service models in order to secure a Cloud service. Part 3 provides summary conclusions, and speculates on the future of Cloud Computing and its associated market.